IMPLEMENTING JIGSAW COOPERATIVE LEARNING IN TEACHING ENGLISH FOR CORRESPONDENCE: STUDENTS’ EXPERIENCES AND CLASSROOM INSIGHTS - Citra Dwi Safitri; A. Kamariah; Musdalifah (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
Student-centered learning has become increasingly important in English for Specific Purposes (ESP) courses to encourage active participation and collaborative knowledge construction. However, classroom instruction in correspondence writing often remains teacher-centered, limiting students' opportunities to engage in meaningful interaction and peer learning. This study explored how a cooperative learning strategy was implemented in an undergraduate correspondence course by examining students' learning experiences and classroom interaction. A descriptive qualitative design was employed involving two undergraduate classes at Applied English Study Program, Universitas Negeri Makassar. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using thematic analysis. The findings revealed that the learning activities enabled students to collaboratively develop their understanding of request letters and complaint letters through structured peer teaching and group discussion. Students reported positive learning experiences, highlighting improved understanding of the lesson, increased responsibility for learning, and greater confidence in explaining concepts to peers. Classroom observations further showed active interaction characterized by discussion, questioning, knowledge sharing, and peer feedback throughout the learning process. These findings suggest that cooperative learning provides a practical approach for creating a more interactive and collaborative learning environment in ESP correspondence courses while supporting meaningful student engagement and peer-assisted learning.